Assessing patterns of change in lifestyle behaviours by parity: a longitudinal cohort study. (1st July 2022) - Makama, Maureen; Earnest, Arul; Lim, Siew; Skouteris, Helen; Hill, Briony; Teede, Helena; Boyle, Jacqueline A; Brown, Wendy J; Hodge, Allison M; Moran, Lisa J
Abstract: Background: The time constraints and reprioritization of personal health associated with having children may lead women to adopt less healthy lifestyles. We assessed the patterns of change in weight and lifestyle behaviours associated with having children and whether these differ between primiparous and multiparous women. Methods: Data were from Surveys 3 and 5 of the 1973–1978 birth cohort of the Australian Longitudinal Study on Women's Health. In women who were nulliparous at Survey 3, we assessed changes in weight, energy intake, diet (diet quality, macronutrients and micronutrients), physical activity and sitting time by parity status at Survey 5 using one-way analysis of covariance. Results: Of 4927 eligible women, 2503 gave birth (1090 primiparous and 1413 multiparous) by Survey 5. Women who had given birth 6 years later increased weight (1.0 kg; 95% CI 0.5, 1.5), energy intake (833.9 kJ/day; 95% CI 706.7, 961.1) and diet quality (1.5 units; 95% CI 0.8, 2.1), but decreased physical activity [–405.0 Metabolic Equivalent of Task.min/week; 95% CI –464.2, –345.8] and sitting time (–1.8 h/day; 95% CI –1.9, –1.6) (adjusted mean differences) relative to those who remained nulliparous. In subgroup analysis involving further stratification by parity, the increase in diet quality was only seen in women who became primiparous and the decrease in sitting time was more marked in multiparous women. Conclusion: Childbearing is associated with increased weight and energy intake, decreased physical activity, increased diet quality and decreased sitting time. More research targeting weight, energy intake and physical activity for improvement in women during the childbearing years is warranted.